Effect of porcine placental extract on the mild menopausal symptoms of climacteric women. (4th March 2017) - Kitanohara, M.; Yamamoto, T.; Masunaga, S.; Ohishi, M.; Komatsu, Y.; Nagase, M.
Abstract: Objectives: This study assessed the effects of oral porcine placental extract (PPE) on the mild menopausal symptoms of climacteric women. Methods: In this 12-week, multicenter, randomized, double-blind, placebo-controlled, parallel-group study, 50 climacteric Japanese women were randomized 1 : 1 to oral PPE (300 mg/day) or placebo. Menopausal symptoms were evaluated by using the Simplified Menopausal Index (SMI), as were serum estradiol (E2) and follicle stimulating hormone (FSH) levels. Blood biochemical and cellular and urinary tests were done to evaluate safety aspects of repeated oral administration of PPE. Results: The total SMI score of the PPE group was significantly more improved after 12 weeks than that of the placebo group ( p = 0.031). This score and three subscores (vasomotor, psychological, and somatic symptoms) were significantly improved at 8 and/or 12 weeks compared with the initial values in the PPE group ( p < 0.05). E2 and FSH levels were not improved in either group. No adverse events were observed. Conclusions: Oral PPE at 300 mg/day improved the mild menopausal symptoms of climacteric women. Since oral PPE did not improve serum E2 and FSH levels, PPE is thought not to ameliorate hormonal balance itself but to improve subjective feelings of climacteric women.